MiR-130a in the adipogenesis of human SGBS preadipocytes and its susceptibility to androgen regulation. (1st January 2020) - Greither, Thomas; Wenzel, Carina; Jansen, Julia; Kraus, Matthias; Wabitsch, Martin; Behre, Hermann M.
ABSTRACT: Objectives : Adipogenesis is the differentiation process generating mature adipocytes from undifferentiated mesenchymal stem cells. The differentiation can be inhibited by androgens, although knowledge about intracellular effectors of this inhibition is scarce. Recently, androgen-regulated microRNAs were detected as interesting candidates in this context. In this study, we analyse the role of miR-130a and miR-301 in the adipogenesis of human SGBS preadipocytes and whether they are prone to androgen regulation. Materials and Methods : microRNA expression during adipogenic differentiation with or without androgen stimulation was measured by qPCR. Putative target genes of miR-130a and miR-301 were identified by target database search and validated in luciferase reporter assays. Results : miR-130a and miR-301 are both significantly downregulated on day 3 and day 5 of adipogenic differentiation in comparison to day 0. Under androgen stimulation, a significant upregulation of miR-130a was detected after 7 days of adipogenesis lasting to day 14, while miR-301 did not change significantly until day 14. Luciferase reporter assays revealed the androgen receptor (AR), adiponectin (ADIPOQ) and tumour necrosis factor alpha (TNFα) as miR-130a target genes. Conclusions : miR-130a is an androgen-regulated microRNA that is downregulated during the early phase of adipogenesis and exerts its functions by regulating AR and ADIPOQ translation. These data may help to identify new signalling pathways associated with the androgen-mediated inhibition of adipogenesis.